Development of Experiment-Based IPAS Exploration Sheet (LEPAS) on the Material of the Effect of Force on Objects - Rena Dwi Wulandari; Woro Sri Hastuti; Mar’atu Zahra; Syifa Nurul; Ika Damayanti; Attar Nazaruddin Mirza; Intan Purnama Dewi (Jurnal Penelitian Pendidikan IPA, 2025)
The learning process will be effective if supported by learning media that is right on target and based on student needs analysis. LEPAS (Student Exploration Sheet) as a learning media is characterized by integrated activities with traditional games as activities. In addition, LEPAS has the advantage that the activities carried out are able to foster student experimentation but use simple experimental materials so that they are easily implemented by students. Experimental science is a very suitable learning method to be applied in science learning. This research uses the RND method by developing LEPAS. The 4D RND model was chosen as the development model. The research subjects were fourth grade students of SD Al Islam Yogyakarta and their class teachers. The results showed that the LEPAS media that had been developed had received validation by experts with the results of the percentage of material validation of 95%, media 90.66%, language 88.33% with a very valid category. Based on the needs analysis, the results show that the developed media is very suitable for grade IV elementary school because this media accommodates the needs of students, especially in science learning which requires experiment-based activities. LEPAS is declared feasible to use as media in Class IV based on the analysis of student needs to accommodate experimental learning.